Talent management in the system of administrating economic security of a university - Storozhuk, O.; Zaiarniuk, O.; Сторожук, О. В.; Заярнюк, О. В. (OKTAN PRINT s.r.o., 2019)
The article discusses the relevance of the talent management direction in modern personnel management of Ukraine’s universities. Talent management is considered as a modern approach to improve the efficiency of universities. Authors analyses the impact of talent management technologies on improving the economic security of universities. The article identifies negative factors that influence efficiency of the measures on talent management. Authors developed and presented recommendations for the management of talented personnel to improve economic security and competitiveness of universities. This changes work on talent management in accordance with the current needs and strategic goals of universities. A key factor in the use of the concept of talent management is the corporate innovation ecosystem of universities.
Keywords: talents; talent management; university; economic security; young teachers